I believe in Preaching - Stott, John R. W. (London [England] Hodder and Stoughton, 1982)
John Scott reminds us of the glorious heritage and mighty effect of preaching. He tackles contemporary objections to preaching, examines its theological foundations, and highlights the importance of applying biblical truth to the everyday lives of Christi
Keywords: Preaching